Corrosion-inhibiting lubricating additive, composite lubricant and use thereof
Patent Information
- Application Number
- CN202410081453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-19
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-19
AI Technical Summary
本发明提供的缓蚀润滑添加剂,解决无机硼酸盐在润滑油中分散稳定性差的问题,同时不影响硼酸盐本身的碱性储备,本发明提供的该有机硼酸盐缓蚀润滑添加剂,可用做船机气缸缓蚀润滑添加剂并显著提升润滑油的抗磨性能
[0024]本发明提供的缓蚀润滑添加剂,不仅解决了无机硼酸盐在润滑油中分散稳定性差的问题,而且不影响硼酸盐本身的碱性储备,该缓蚀润滑添加剂可在润滑油中长时间稳定分散,同时保持良好的碱性储备;并且,其添加于润滑油中使用,具有优异的动态减摩抗磨性能和静态缓蚀效果,因此,其可用做船机气缸缓蚀润滑添加剂,并显著提升润滑油的抗磨性能。
Smart Images

Figure CN117965226B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lubricant additives, and particularly to a corrosion-inhibiting lubricant additive, a composite lubricant, and their applications. Background Technology
[0002] The IMO requires that, starting January 1, 2020, the sulfur content of marine fuel oil must not exceed 0.5%. However, relevant cases show that the application of low-sulfur fuel oil reduces the reliability and stability of diesel engine operation, which is directly reflected in the reduced performance of diesel engine cylinder liners; and the reasons for abnormal wear on the cylinder liner surface when using low-sulfur fuel oil include:
[0003] Improper management and maintenance can lead to a mismatch between the pH of the lubricating oil and its pH. When the oil is "too acidic," the cylinder liner is prone to corrosion and wear, which accelerates the loss of cylinder liner material and the generation of abrasive particles. As water and oxides mixed into the cylinder oil gradually accumulate, chemical or electrochemical corrosion occurs on the metal surface, further deteriorating the working condition of the cylinder liner. The catalyst used in fuel hydrorefining introduces hard particles, which exacerbates abrasive wear on the cylinder liner surface.
[0004] Using corrosion-inhibiting lubricating additives is one of the most economical methods to reduce cylinder liner friction and material loss. Common marine anti-friction and anti-wear additives, such as organic molybdenum additives and zinc dialkyl thiophosphate, can significantly reduce cylinder liner friction and wear, and improve engine power. Furthermore, to address the problem of increased lubricating oil acidity due to the accumulation of combustion products and oil oxidation, most manufacturers add alkaline additives such as calcium alkylphenol sulfide to cylinder lubricating oil. These sulfur-containing additives have good alkalinity reserves and excellent lubrication performance, effectively inhibiting corrosion and wear and improving cylinder liner lubrication. However, using sulfur-containing additives not only increases harmful engine emissions but also introduces additional sulfate ash into the combustion chamber, increasing the risk of piston deposits and seizure. In addition, the copper corrosion phenomenon of sulfur-containing additives also limits their further use.
[0005] In contrast, boron-based additives such as organoborates and borates are sulfur-free and have low ash content, making them potential alternatives to sulfur-based additives. Among them, organoborates have good oil solubility and excellent friction-reducing, wear-resistant, and rust-preventing functions, but their poor hydrolytic stability and relatively singular functions make it difficult to meet the increasingly complex working conditions.
[0006] Unlike organic borate esters, inorganic borate esters possess excellent alkalinity reserves, extreme pressure lubrication properties, and thermal oxidation stability, making them ideal materials for cylinder oil additives. However, the application of borate esters in lubricating oils is limited by particle agglomeration and sedimentation. Therefore, most manufacturers use large amounts of dispersants to improve the dispersion of borate esters in oil, but this dispersion system has poor stability and is prone to precipitation. Compared to the above-mentioned dispersant addition scheme, surface modification of borate esters using commonly used fatty acid oiliness agents can achieve lipophilic modification of inorganic borate esters, thereby improving the dispersion stability of borate esters in lubricating oils.
[0007] However, for borates themselves, their surfaces only have a small number of hydroxyl functional groups as active sites for chemical bonding, making it difficult for traditional fatty acid modifiers to form stable surface modification structures based primarily on covalent principles. Furthermore, the adsorption and encapsulation layers formed by these modifiers through non-covalent interactions such as electrostatic attraction and intermolecular forces may hinder the contact between borates and acidic media, adversely affecting the basicity reserves of borates themselves.
[0008] Therefore, how to improve organic borates to solve the problem of poor dispersion stability of inorganic borates in lubricating oil, while not affecting the alkalinity of the borates themselves, is a technical challenge that those skilled in the art are committed to solving. Summary of the Invention
[0009] To address the shortcomings of the prior art mentioned in the background section, this invention provides a corrosion-inhibiting lubricating additive. The corrosion-inhibiting lubricating additive provided by this invention solves the problem of poor dispersion stability of inorganic borates in lubricating oil, while not affecting the alkalinity reserve of the borates themselves. This organic borate corrosion-inhibiting lubricating additive provided by this invention can be used as a corrosion-inhibiting lubricating additive for marine engine cylinders and significantly improves the anti-wear performance of lubricating oil.
[0010] The corrosion-inhibiting and lubricating additive is formed by chemically bonding a monoalkyl diol to the surface of a borate (i.e., the hydroxyl groups of the monoalkyl diol are grafted onto the surface of the borate via BOC). The particle size of the corrosion-inhibiting and lubricating additive is between 200 and 300 nm. The monoalkyl diol has 8 to 20 carbon atoms, and the mass ratio of the borate to the monoalkyl diol is 5:1 to 20:1.
[0011] In some embodiments, the monoalkyl diol includes one or more combinations of lauryl glycol, octyl glycol, and nonyl glycol; the borate includes one or more combinations of magnesium borate, calcium borate, and zinc borate.
[0012] In some embodiments, the corrosion-inhibiting lubricating additive is prepared by the following steps:
[0013] Borate and monoalkyl diol are mixed to obtain mixture M1;
[0014] The mixture M1 is ball-milled to obtain a ball-milled mixture, wherein a high-voltage discharge treatment is performed during the ball-milling process;
[0015] The cooled ball-milled mixture is mixed evenly with a hydrocarbon solvent, and the solid phase is collected after solid-liquid separation to obtain the corrosion-inhibiting and lubricating additive; wherein the monoalkyl diol has 8 to 20 carbon atoms, and the mass ratio of the borate to the monoalkyl diol is 5:1 to 20:1.
[0016] In some embodiments, high-voltage discharge treatment is performed during the ball milling process; wherein the discharge voltage is (21-23) KV, the discharge gas is one or more combinations of Ar and He, the pressure inside the ball mill jar is (0.02-0.04) MPa, the vertical vibration frequency of the ball mill is (20-25) Hz, the amplitude is (10-12) mm, and the ball milling time is (8-12) h.
[0017] In some embodiments, the hydrocarbon solvent includes one or more combinations of petroleum ether, n-pentane, and toluene; the mass ratio of the ball-milled mixture to the hydrocarbon solvent is (1:1) to (1:200).
[0018] In some embodiments, the cooled ball-milled mixture is mixed evenly with the hydrocarbon solvent to obtain mixture M2; mixture M2 is ultrasonically vibrated and then allowed to settle naturally to remove large particles in the lower layer; the upper layer solution is then centrifuged; the solid product obtained by centrifugation is dried to obtain the corrosion-inhibiting lubricating additive.
[0019] The present invention also provides a composite lubricating oil, the components of which include lubricating oil and corrosion-inhibiting lubricating additives; the corrosion-inhibiting lubricating additives described above are used.
[0020] In some embodiments, the amount of the corrosion-inhibiting lubricating additive is 0.05% to 2% of the mass of the composite lubricating oil.
[0021] The present invention also provides the application of the composite lubricating oil described above in cylinder liner lubrication.
[0022] The present invention also provides the application of the composite lubricant described above in metal-metal, metal-polymer or metal-ceramic friction pairs.
[0023] Based on the above, compared with the prior art, the corrosion-inhibiting lubricating additive provided by the present invention has the following beneficial effects:
[0024] The corrosion-inhibiting lubricating additive provided by this invention not only solves the problem of poor dispersion stability of inorganic borates in lubricating oil, but also does not affect the alkalinity reserve of borates themselves. This corrosion-inhibiting lubricating additive can be stably dispersed in lubricating oil for a long time while maintaining good alkalinity reserve. Furthermore, when added to lubricating oil, it has excellent dynamic friction-reducing and anti-wear properties as well as static corrosion inhibition effects. Therefore, it can be used as a corrosion-inhibiting lubricating additive for marine engine cylinders and significantly improves the anti-wear performance of lubricating oil.
[0025] Other features and beneficial effects of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other beneficial effects of the invention can be realized and obtained by means of the structures particularly pointed out in the description, claims and drawings. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Unless otherwise specified, the positional relationships shown in the drawings in the following description are based on the direction in which the components are drawn in the figure.
[0027] Figure 1 SEM images of raw magnesium borate, oil-based magnesium borate, and molten magnesium borate;
[0028] Figure 2 The settling state diagrams of the composite lubricating oil after different settling times are shown.
[0029] Figure 3 The FTIR spectra of original magnesium borate, oil-based magnesium borate, and molten magnesium borate are shown.
[0030] Figure 4 A graph showing the pH changes when different concentrations of corrosion-inhibiting and lubricating additives are added to a 0.5% H2SO4 solution;
[0031] Figure 5 The friction coefficient curves of HT200 in different lubricating media at 150℃ are shown.
[0032] Figure 6 The graph shows the average friction coefficient and wear volume data of HT200 in different lubricating media at 150℃.
[0033] Figure 7 Macroscopic state diagrams of HT200 friction pairs under different lubricating media at 150℃;
[0034] Figure 8 SEM morphology and EDS energy dispersive spectroscopy of HT200 wear surface in sulfuric acid degraded oil lubricating medium at 150℃;
[0035] Figure 9 SEM morphology and EDS energy dispersive spectroscopy of HT200 wear surface in sulfuric acid degraded oil / oil-magnesium borate lubricating medium at 150℃;
[0036] Figure 10 SEM morphology and EDS energy dispersive spectroscopy of HT200 wear surface in sulfuric acid deteriorated oil / month-magnesium borate lubricating medium at 150℃;
[0037] Figure 11 The SEM morphology and EDS spectrum of the HT200 wear surface in sulfuric acid deteriorated oil / T115B lubricating medium at 150℃ are shown. Detailed Implementation
[0038] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. The technical features designed in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0039] In the description of this invention, it should be noted that all terms used in this invention (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and should not be construed as limiting the invention; it should be further understood that the terms used in this invention should be understood to have the same meaning as those in the context of this specification and in the relevant field, and should not be understood in an idealized or overly formal sense, except as expressly defined in this invention.
[0040] This invention provides an operational example of a method for preparing a corrosion-inhibiting lubricating additive, which includes the following steps:
[0041] (1) Mix borate and monoalkyl diol to obtain mixture M1;
[0042] The monoalkyl diol has 8 to 20 carbon atoms, and the mass ratio of the borate to the monoalkyl diol is 5:1 to 20:1. Optionally, the monoalkyl diol includes one or more combinations of lauryl glycol, octanediol, and nonanediol; the borate includes one or more combinations of magnesium borate, calcium borate, and zinc borate.
[0043] (2) The mixture M1 is ball-milled to obtain a ball-milled mixture;
[0044] The ball milling process involves high-voltage discharge treatment, wherein the discharge voltage is (21-23) KV, the discharge gas is one or more combinations of Ar and He, the pressure inside the ball mill jar is (0.02-0.04) MPa, the vertical vibration frequency of the ball mill is (20-25) Hz, the amplitude is (10-12) mm, and the ball milling time is (8-12) h.
[0045] (3) Mix the cooled ball-milled mixture with a hydrocarbon solvent to obtain mixture M2;
[0046] The mass ratio of the ball-milled mixture to the hydrocarbon solvent is (1:1) to (1:200); optionally, the hydrocarbon solvent includes one or more combinations of petroleum ether, n-pentane, and toluene.
[0047] (4) After ultrasonically vibrating the mixture M2, let it stand to allow it to settle naturally, remove the large particles of sediment in the lower layer, and take the upper layer solution for centrifugation.
[0048] (5) The solid product obtained by centrifugation is dried to obtain the corrosion inhibitor and lubricant additive; wherein the drying temperature is 85-90℃.
[0049] To verify the effectiveness of the present invention, the following examples and comparative examples using oleic acid as a modifying agent are provided for comparison:
[0050] Example 1:
[0051] Step a: After thoroughly mixing 10g of magnesium borate and 1g of lauryl glycol (1,2-dodecanediol) powder, the mixture is subjected to high-energy ball milling. High-voltage discharge treatment is performed during the ball milling process, with a discharge voltage of 22KV. Ar gas is filled into the milling jar as the discharge gas, and the pressure inside the jar is controlled at 0.03Mpa. The vertical vibration frequency of the ball mill is 22Hz, the amplitude is 10mm, and the milling time is 10h.
[0052] Step b: Mix the cooled ball-milled mixture with petroleum ether at a mass ratio of 1:1, ultrasonically vibrate for 2 hours, place in a centrifuge tube, let stand for 5 minutes to allow it to settle naturally, remove the large particles in the lower layer, and centrifuge the upper layer solution at 9500 r / m for 30 minutes using a Xiangyi H1850 benchtop high-speed centrifuge. Dry the centrifuged product at 90℃ to obtain the powder, which is the lauryl glycol-magnesium borate additive (hereinafter referred to as lauryl-magnesium borate additive).
[0053] Comparative Example 1:
[0054] Step a: Using 300ml of oleic acid as the wet grinding medium and modifier, 10g of magnesium borate powder was subjected to high-energy ball milling. High-voltage discharge treatment was performed during the ball milling process, with a discharge voltage of 25KV. Ar gas was filled into the ball mill jar as the discharge gas, and the pressure inside the jar was controlled at 0.03Mpa. The vertical vibration frequency of the ball mill was 22Hz, the amplitude was 10mm, and the ball milling time was 10h.
[0055] Step b: Mix the cooled ball-milled mixture with petroleum ether at a mass ratio of 1:1, ultrasonically vibrate for 2 hours, place in a centrifuge tube, let stand for 5 minutes to allow it to settle naturally, remove the large particles in the lower layer, and centrifuge the upper layer solution at 9500 r / m for 30 minutes using a Xiangyi H1850 benchtop high-speed centrifuge. Dry the centrifuged product at 90℃ to obtain the powder, which is the oleic acid-magnesium borate additive (hereinafter referred to as oleic acid-magnesium borate additive).
[0056] The performance of the additive products obtained in Example 1 and Comparative Example 1 was tested:
[0057] 1. Microstructure observation:
[0058] (1) Test method:
[0059] The microstructures of pristine magnesium borate, oleo-magnesium borate, and tert-magnesium borate (Example 1) were observed using a Carl Zeiss (Germany) SIGMA500 scanning electron microscope.
[0060] (2) Test Results
[0061] For detailed results, please see [link / details]. Figure 1 ,in, Figure 1 (a)-(c) are SEM images of the original magnesium borate, oil-based magnesium borate, and molten magnesium borate (Example 1), respectively; Figure 1 As shown in (a), the original magnesium borate consisted of whiskers 5-10 μm long; from Figure 1 (b) It can be seen that the oleic acid-modified magnesium borate (Comparative Example 1) is an agglomerate of long whiskers and particles (0.5-5 μm); from Figure 1 (c) It can be seen that the magnesium borate prepared by the method of the present invention (Example 1) consists of small particles with a particle size of 200-300 nm, and the refining effect is better.
[0062] 2. Dispersion stability
[0063] (1) Test method:
[0064] Two additives, oil-magnesium borate (Comparative Example 1) and mol-magnesium borate (Example 1), were added to 500N base oil at concentrations of 0.01%, 0.05%, and 0.5% (m / v), respectively. The composite oils were ultrasonically vibrated for 2 hours using an SB 100D ultrasonic vibrator from Shanghai Shengxi Instrument Co., Ltd. The dispersion stability of different lubricating additives in 500N base oil was compared by allowing them to settle.
[0065] (2) Test Results
[0066] For the dispersion stability of 1-Mg-borate (Example 1) and 1-Mg-borate in 500N base oil, please refer to [link to documentation]. Figure 2 Result; among which, Figure 2 (a)-(f) show the settling states of the composite oil after standing for 0h, 48h, 96h, 144h, 192h, and 240h, respectively. The composite oil samples are placed in the following order from left to right: 500N base oil, composite oil with 0.01% magnesium borate (Example 1), composite oil with 0.01% magnesium borate, composite oil with 0.1% magnesium borate (Example 1), composite oil with 0.1% magnesium borate, composite oil with 0.5% magnesium borate (Example 1), and composite oil with 0.5% magnesium borate.
[0067] Depend on Figure 2 (a) It can be seen that: when no settling is performed after the shaking treatment, the 500N base oil is colorless, while the compound oil with additives is dark black; after a period of settling, the oil state is as follows: Figure 2 As shown in (b) 48h, (c) 96h, (d) 144h, (e) 192h, and (f) 240h, it is evident that the dispersion stability of molten magnesium borate (Example 1) at the same concentration is significantly better than that of oil-magnesium borate.
[0068] 3. FTIR spectral characterization:
[0069] (1) Test method:
[0070] The surface functional groups of magnesium borate before and after modification were analyzed using a NICOLET IS10 infrared spectrometer from Thermo Fisher Scientific, USA, and the FTIR spectra of each lubricating additive were obtained.
[0071] (2) Test Results
[0072] Figure 3 The FTIR spectra of the original magnesium borate, oil-based magnesium borate (Comparative Example 1), and molten magnesium borate (Example 1) are shown.
[0073] from Figure 3 As can be seen, compared with the original magnesium borate spectrum, the oil-magnesium borate generally retains the original spectral characteristics; the oil-magnesium borate (Example 1) spectrum shows significant changes in several places and at 1333 cm⁻¹-1 The detection of the BOC stretching vibration peak indicates that the (-CH2-) group is grafted onto the magnesium borate surface via BOC.
[0074] 4. Alkaline reserves
[0075] (1) Test method:
[0076] Two additives, oil-magnesium borate (Comparative Example 1) and molten magnesium borate (Example 1), were added to a 0.5% sulfuric acid solution at concentrations of 0.1%, 0.3%, 0.5%, 0.7%, and 0.9%, respectively. The pH value of the solution was measured using a PHS-25 precision pH meter from Shanghai Instrument & Electronics Scientific Instrument Co., Ltd., to compare the alkalinity reserves of different lubricating additives.
[0077] (2) Test Results
[0078] like Figure 4 As shown (the horizontal axis represents the additive concentration, and the vertical axis represents the pH value), the pH value of the solution containing magnesium borate (Example 1) at the same concentration is significantly higher than that after adding magnesium borate, indicating that the alkalinity reserve of magnesium borate (Example 1) is significantly better than that of magnesium borate.
[0079] 5. Wear volume
[0080] (1) Test method:
[0081] A reciprocating tribological experiment was conducted on the CFT-I type material surface performance comprehensive tester of China Kaihua Instrument Equipment Co., Ltd. The friction pair was made of cylinder liner material HT200, the thrust plate diameter was 30mm and the pin diameter was 4mm. The contact surfaces were polished to a smooth surface using sandpaper of different grits (400#, 600#, 800# and 1200#).
[0082] 1.5% deionized water and 0.5% sulfuric acid (80% concentration) were added to 500N base oil, and the mixture was sonicated for 1 hour to obtain sulfuric acid-degraded oil. Then, 0.5% oleo-magnesium borate (Comparative Example 1), 0.5% oleo-magnesium borate (Example 1), and 0.5% T115B (i.e., commercially available additive detergent dispersant T115B) were added to the sulfuric acid-degraded oil, and the mixture was sonicated for 1 hour to obtain three mixed oils. High-temperature tribological experiments were conducted on the sulfuric acid-degraded oil and the three mixed oils under a load of 150N, a reciprocating frequency of 5Hz, and a temperature of 150℃. The coefficient of friction of HT200 under different environments was obtained, and the wear volume was measured using a VK-X250 shape measurement laser microscope from Keyence (China) Co., Ltd.
[0083] (2) Test Results
[0084] like Figure 5As shown, the friction coefficient of HT200 after using magnesium borate (Example 1) is around 0.046, which is at a relatively low level. The friction coefficient curve of HT200 in the sulfuric acid deteriorated oil / magnesium borate (Example 1) has the highest stability. This is because the fatty alcohol carried by magnesium borate (Example 1) plays a role in linking the oil-water interface and stabilizing the oil state.
[0085] in, Figure 6 From left to right, the data represent the average coefficient of friction and wear volume of sulfuric acid degraded oil, sulfuric acid degraded oil / oil-magnesium borate, sulfuric acid degraded oil / oil-magnesium borate (Example 1), and sulfuric acid degraded oil / T115B. Figure 6 visible:
[0086] Compared to the additive-free version (sulfuric acid-degraded oil), oil-magnesium borate reduced the average coefficient of friction of HT200 by 20.5%, but failed to achieve anti-wear properties. Magnesium borate (Example 1) reduced the average coefficient of friction and wear volume of HT200 by 32.8% and 20.7%, respectively, while T115B reduced the average coefficient of friction and wear volume of HT200 by 38.9% and 18.9%, respectively. It is evident that the friction-reducing and anti-wear properties of magnesium borate (Example 1) and the commercial additive T115B are comparable and significantly superior to those of oil-magnesium borate.
[0087] 6. Static corrosion inhibition effect
[0088] (1) Test method:
[0089] The HT200 friction pair was cleaned with anhydrous ethanol after the high-temperature tribological experiment, and the macroscopic state of the HT200 friction pair under different lubricating media was photographed with a personal camera.
[0090] (2) Test Results
[0091] For detailed results, please see [link / details]. Figure 7 , Figure 7 Figures (a)-(d) correspond to sulfuric acid degraded oil, sulfuric acid degraded oil / oil-magnesium borate, sulfuric acid degraded oil / oil-magnesium borate (Example 1), and sulfuric acid degraded oil / T115B, respectively.
[0092] Depend on Figure 7 As can be seen from (a), (b), and (d), the non-contact surfaces of the friction pairs in the degraded sulfuric acid oil, degraded sulfuric acid oil / oil-magnesium borate, and degraded sulfuric acid oil / T115B are severely corroded. Figure 7 (c) It can be seen that the non-wearing surfaces in the sulfuric acid deteriorated oil / Mg-borate (Example 1) were not corroded and remained clean, indicating that the static corrosion inhibition effect of Mg-borate (Example 1) was good.
[0093] 7. Inhibit sulfuric acid corrosion
[0094] (1) Test method:
[0095] The wear surfaces in the different lubricating media were observed and analyzed using a Carl Zeiss (Germany) SIGMA500 scanning electron microscope.
[0096] (2) Test Results
[0097] See results Figure 8 As shown, Figure 8-11 These correspond to sulfuric acid degraded oil, sulfuric acid degraded oil / oil-magnesium borate, sulfuric acid degraded oil / oil-magnesium borate (Example 1), and sulfuric acid degraded oil / T115B, respectively. The upper figure is the SEM morphology of the HT200 wear surface, and the lower figure is the EDS energy spectrum of the area circled in the upper figure.
[0098] like Figure 8 As shown, without additives, the friction interface is severely corroded, and the pits on the surface contain corrosion residues of C, Fe, O, Si, S, etc.
[0099] Depend on Figure 9 It is evident that the worn surface was still riddled with corrosion pits after the application of oil-magnesium borate. This is because the low alkalinity of oil-magnesium borate prevented it from adequately inhibiting sulfuric acid corrosion.
[0100] Depend on Figure 10-11 As can be seen, no corrosion damage was observed on the wear surface after using magnesium borate (Example 1) and T115B, indicating that both can effectively inhibit the corrosion and wear of HT200. Among them, Figure 10 The wear surface shown did not exhibit obvious wear marks or grooves. This is because magnesium borate (Example 1) forms deposits at surface defects through reciprocating friction, thereby helping to fill wear marks and reduce wear volume. In contrast, from Figure 11 It is evident that even after using T115B, the HT200 wear surface still shows many obvious wear marks and grooves.
[0101] The test results of the original magnesium borate in Example 1 and Comparative Example 1 are summarized in Table 1-2 below:
[0102] Table 1
[0103]
[0104] Table 2
[0105]
[0106]
[0107] To verify the innovativeness of this application's specific ball milling process combined with a specific monoalkyl diol modifier to achieve the desired effect, the following comparative examples are provided:
[0108] Comparative Example 2:
[0109] The only difference between this comparative example and Example 1 is that the ball milling process is replaced by a liquid phase modification process. The process parameters are as follows: prepare 100 ml of 0.05 mol / L lauryl glycol solution (solvent is toluene), add 1 g of magnesium borate powder (magnesium borate to lauryl glycol mass ratio 10:1) that has been preheated to 90°C to 10 ml of lauryl glycol solution in the adsorption tube, sonicate each adsorption tube for 1 h and let it stand for 48 h, separate the excess liquid to obtain the mixture, which is the additive sample of Comparative Example 2; other preparation steps (step b) and conditions are the same as in Example 1.
[0110] The product obtained in Comparative Example 2 was tested using the same testing methods and process parameters as in Example 1, except that the sample was replaced with the product of Comparative Example 2. The results are summarized in Tables 3-4 below:
[0111] Table 3
[0112]
[0113]
[0114] Table 4
[0115]
[0116] Analysis of the data in the table above shows that:
[0117] Compared to Example 1, Comparative Example 2 showed a decrease in dispersion stability and dynamic friction reduction and anti-wear performance, indicating that the lubricating additive prepared by the present invention using specific borate and monoalkyl diol raw materials and a specific processing method can achieve the desired effect.
[0118] Comparative Example 3:
[0119] The only difference between this comparative example and Example 1 is that the mass ratio of the borate to the monoalkyl diol is 30:1 during the ball milling process; the other preparation steps and conditions are the same as in Example 1.
[0120] Comparative Example 4:
[0121] The only difference between this comparative example and Example 1 is that the mass ratio of the borate to the monoalkyl diol is 4:1 during the ball milling process; the other preparation steps and conditions are the same as in Example 1.
[0122] Comparative Example 5:
[0123] The only difference between this comparative example and Example 1 is that the discharge voltage was changed to 20kV during the ball milling process; the other preparation steps and conditions were the same as in Example 1.
[0124] Comparative Example 6:
[0125] The only difference between this comparative example and Example 1 is that the discharge voltage was changed to 30kV during the ball milling process; the other preparation steps and conditions were the same as in Example 1.
[0126] Comparative Example 7:
[0127] The only difference between this comparative example and Example 1 is that the ball milling time is 6 hours during the ball milling process; the other preparation steps and conditions are the same as in Example 1.
[0128] Comparative Example 8:
[0129] The only difference between this comparative example and Example 1 is that the ball milling time is 15 hours during the ball milling process; the other preparation steps and conditions are the same as in Example 1.
[0130] The products obtained in the comparative example were tested using the same testing methods and process parameters as in Example 1, except that the sample in Example 1 was replaced with the product from the comparative example. The results are summarized in Tables 5-6 below:
[0131] Table 5
[0132]
[0133]
[0134] Table 6
[0135]
[0136]
[0137] Analysis of the data in the table above shows that, compared with Example 1, the dispersion stability and dynamic friction reduction and anti-wear performance of Comparative Examples 3-8 are worse. This indicates that the lubricating additive prepared by the embodiment of the present invention using a specific ratio of borate and monoalkyl diol raw materials, combined with a ball milling process with specific parameters, can achieve the desired effect.
[0138] In summary, the analysis of the above test results shows that:
[0139] 1. Summary of Test Results:
[0140] (1) Microstructure and alkaline reserve results:
[0141] This invention, for the first time, uses lauryl glycol (1,2-dodecanediol) as a modifier to surface-modify magnesium borate through high-energy ball milling. Magnesium borate modified with lauryl glycol (1,2-dodecanediol) provided by this invention is refined into particles with a primary particle size of 200-300 nm. Its stable dispersion time in 500N base oil is more than twice that of oleic acid-modified magnesium borate (Comparative Example 1), and its alkalinity reserve is approximately twice that of the latter.
[0142] (2) The results of high-temperature tribological experiments simulating cylinder liner corrosion show that:
[0143] Compared to the absence of additives (sulfuric acid degraded oil), the addition of magnesium borate (Example 1) to the sulfuric acid degraded oil reduced the coefficient of friction and wear volume by 32.8% and 20.7%, respectively. No corrosion or wear damage was observed at the friction interface, and the non-wear surface was bright and clean, close to the state before the experiment.
[0144] Compared to oleic acid-modified magnesium borate (oil-magnesium borate), oleic acid-modified magnesium borate (Example 1) is superior in terms of powder particle size, dispersion stability, alkalinity reserve, and tribological properties.
[0145] Compared to commercially available marine high-alkalinity additive T115B, 1-magnesium borate (Example 1) has comparable dynamic friction reduction and anti-wear properties, and significantly better static corrosion inhibition effects.
[0146] 2. Analyze the test results:
[0147] (1) Experimental studies have found that the solution provided by this invention has good effects on the fine refining of magnesium borate powder, group grafting, and lipophilic modification. The reason for this is:
[0148] This is because lauryl glycol, as a solid-phase modifier, not only did not affect the initial crushing and refining of the additive powder, but also formed an organic modified layer on the surface of magnesium borate by constructing BOC bonds. This covalent modified layer is stable in high-energy ball milling and inhibits particle agglomeration through the repulsion of surface group charges (see...). Figure 1 , Figure 2 ).
[0149] The fine and dispersed (non-agglomerated) lubricant additive powder is conducive to the long-term stable dispersion of the lubricant additive powder in the lubricating oil, which lays the foundation for its full participation in the friction interface and exerting the friction reduction and anti-wear effect.
[0150] (2) Experimental studies have shown that compared with oil-magnesium borate (Comparative Example 1), the oil-magnesium borate provided by the present invention (Example 1) has a longer stable dispersion time in lubricating oil.
[0151] This is because the magnesium borate particles modified with lauryl glycol exhibit reduced agglomeration and smaller particle size. Under the influence of steric hindrance and the repulsion of surface group charges, the stable dispersion time of lauryl-magnesium borate (Example 1) is longer (see Example 1). Figure 3 ).
[0152] (3) Experimental studies have found that the alkalinity reserve of the molten magnesium borate (Example 1) provided by the present invention is significantly stronger than that of the molten magnesium borate (Comparative Example 1).
[0153] This is because the lipophilic groups of oleo-magnesium borate adhere to its surface through electrostatic attraction or intermolecular forces, affecting acid-base contact. In contrast, the surface groups of oleo-magnesium borate (Example 1) undergo desorption via acid-catalyzed dissociation of BOC, exposing the inner alkaline components. Therefore, the alkalinity reserve of oleo-magnesium borate (Example 1) is significantly higher than that of oleo-magnesium borate (see...). Figure 4 ).
[0154] (4) Experimental studies have found that, compared with commercially available marine high-alkalinity additive T115B, 1-magnesium borate (Example 1) has comparable dynamic friction reduction and anti-wear performance, and better static corrosion inhibition effect.
[0155] This is because the colloidal structure of T115B itself restricts the effective contact between the alkaline component and the acid. Therefore, magnesium borate-1 (Example 1) has a better static corrosion inhibition ability than T115B (see Example 1). Figure 5 , Figure 6 , Figure 7 ).
[0156] (5) Experimental studies have shown that mol-magnesium borate (Example 1) significantly improved the tribological properties of cylinder liner material (HT200) in a simulated sulfuric acid environment, while mol-magnesium borate (Comparative Example 1) reduced the friction coefficient of HT200 but failed to achieve wear resistance.
[0157] This is because molten magnesium borate (Example 1) effectively inhibits corrosion and wear through acid-base neutralization and film deposition, significantly reducing friction and wear. In contrast, the low alkalinity of molten magnesium borate prevents it from fully neutralizing acidic substances, resulting in severe corrosion and wear and a higher wear volume (see...). Figure 5 , Figure 6 , Figure 8-11 ).
[0158] (6) Experimental studies have found that, compared with Comparative Example 2, where the ball milling process was replaced by the liquid phase modification process, and Comparative Examples 3-8, where the raw material ratio and ball milling process parameters exceeded the limits of this application, the dispersion stability and dynamic friction reduction and anti-wear properties of the magnesium borate (Example 1) provided by the present invention were significantly improved.
[0159] In summary, the key innovative design features and superior effects of the lubricant additive solution provided by this invention are as follows:
[0160] Innovative design features:
[0161] (1) This invention uses borates as the main component and selects a monoalkyl diol as a modifier to obtain an organic borate additive through high-energy ball milling. This monoalkyl diol can form an organic modification layer on the surface of borates by constructing BOC bonds. This modification structure exists stably during ball milling and prevents particle agglomeration, thereby promoting the refinement of powder and realizing the lipophilic modification of borates.
[0162] (2) Due to the pH-sensitive nature of BOC, the surface groups of borate complete desorption in an acidic environment, thus avoiding hindering the contact between the inner borate layer and the acidic corrosive substances, thereby preserving the good alkalinity reserve of borate itself.
[0163] (3) The present invention provides a lubricating additive prepared by a ball milling process with specific parameters using a specific ratio of borate and monoalkyl diol to achieve the desired effect.
[0164] Beneficial effects:
[0165] Compared with the solution of fatty acid-modified inorganic borates which result in poor alkalinity reserves, the lubricating additive solution provided by the present invention not only solves the problem of poor dispersion stability of inorganic borates in lubricating oil, but also does not affect the alkalinity reserves of borates themselves.
[0166] Compared with fatty acid-modified inorganic borate additives, its dynamic friction reduction and anti-wear performance and static corrosion inhibition effect are significantly improved; compared with commercially available marine high-alkalinity additive T115B, the dynamic friction reduction and anti-wear performance of this invention is comparable, and its static corrosion inhibition effect is better.
[0167] The lubricating additive prepared by this invention can be stably dispersed in lubricating oil for a long time while maintaining good alkalinity reserves; and when added to lubricating oil, it has excellent dynamic friction reduction and anti-wear properties and static corrosion inhibition effect. Therefore, it can be used as a lubricating additive for marine engine cylinders and significantly improves the anti-wear performance of lubricating oil.
[0168] It should be noted that:
[0169] This lubricating additive can be used alone or in combination with other lubricating additives.
[0170] In the embodiments of the present invention, 500N base oil, sulfuric acid degraded oil and lubricating additives are respectively used to form composite lubricating oils. According to the design concept of the present invention, the lubricating additives provided by the present invention can be used in combination with other existing base lubricating oils, including but not limited to the 500N base oil and sulfuric acid degraded oil used in the embodiments.
[0171] In this article, “~” is used to represent a numerical range, and the range of this expression includes two endpoint values;
[0172] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific or preferred embodiments under the concept of the present invention, and are not intended to limit it; those skilled in the art can make adaptive adjustments within the concept and protection scope of the present invention.
[0173] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A corrosion-inhibiting and lubricating additive, characterized in that, The corrosion-inhibiting and lubricating additive is formed by chemically bonding a monoalkyl diol to the surface of a borate, and the particle size of the corrosion-inhibiting and lubricating additive is between 200 and 300 nm. The corrosion-inhibiting and lubricating additive is prepared by the following steps: A mixture of borate and monoalkyl diol is obtained as mixture M1. Mixture M1 is then ball-milled to obtain a ball-milled mixture. During the ball-milling process, a high-voltage discharge is performed at a voltage of (21-23) kV. The discharge gas is one or more combinations of Ar and He. The pressure inside the ball mill is (0.02-0.04) MPa. The vertical vibration frequency of the ball mill is (20-25) Hz, the amplitude is (10-12) mm, and the milling time is (8-12) h. The mass ratio of the borate to the monoalkyl diol is 5:1 to 20:
1. The monoalkyl diol includes one or more combinations of lauryl glycol, octanediol, and nonanediol. The borate includes one or more combinations of magnesium borate, calcium borate, and zinc borate. The cooled ball-milled mixture is mixed evenly with a hydrocarbon solvent to obtain mixture M2; mixture M2 is ultrasonically vibrated and then allowed to settle naturally to remove large particles in the lower layer. The upper layer solution is then centrifuged; the solid product obtained by centrifugation is dried to obtain the corrosion-inhibiting and lubricating additive; the hydrocarbon solvent includes one or more combinations of petroleum ether, n-pentane, and toluene; the mass ratio of the ball-milled mixture to the hydrocarbon solvent is (1:1) to (1:200).
2. A composite lubricating oil, characterized in that: Its components include lubricating oil and corrosion-inhibiting lubricating additives as described in claim 1.
3. The composite lubricating oil according to claim 2, characterized in that: The amount of the corrosion-inhibiting lubricating additive is 0.05% to 2% of the mass of the composite lubricating oil.
4. The application of the composite lubricating oil as described in claim 2 in cylinder liner lubrication.
5. The application of the composite lubricant as described in claim 2 in metal / metal, metal / polymer, or metal / ceramic friction pairs.
Citation Information
Patent Citations
Method for preparing nano flaky zinc borate powder
CN102659132A
Surface modified nanometer material serving as lubricating oil additive as well as preparation method and application thereof
CN103804960A
Preparation method for graphene-coated spherical metal
CN110643407A